2017
DOI: 10.1049/iet-map.2015.0745
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐band MIMO dielectric resonator antenna for WiMAX/WLAN applications

Abstract: In this study, a novel dual‐band multiple‐input multiple‐output (MIMO) rectangular dielectric resonator antenna (DRA) for Worldwide interoperability for microwave access (WiMAX) (3.4–3.7) GHz and wireless local area network (WLAN) (5.15–5.35) GHz applications is proposed and investigated. The design operates at fundamental TEδ11x, TE1δ1y and higher order TEδ21x, TE2δ1y modes, excited through two coaxial probes, symmetrically placed adjacent to the DRA. A compact design is achieved by stacking a high permittivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 28 publications
(33 reference statements)
0
84
0
Order By: Relevance
“…From Figure C, it can be observed that the surface current is mainly concentrated over the excited port. As a result, the proposed radiator achieves high isolation between port 1 and port 2 …”
Section: Investigation Of Proposed Antennamentioning
confidence: 95%
“…From Figure C, it can be observed that the surface current is mainly concentrated over the excited port. As a result, the proposed radiator achieves high isolation between port 1 and port 2 …”
Section: Investigation Of Proposed Antennamentioning
confidence: 95%
“…It vastly satisfies the demand of below 0.5 . The diversity gain (DG) is another parameter to evaluate the performance of MIMO antenna and it can be calculated as: italicDG=1010.99ρe2 …”
Section: Resultsmentioning
confidence: 99%
“…The 3‐db bandwidth is not significantly affected by air gap . Air gap is also used for better impedance matching . Effect of copper strips on simulated IBW and gain of DRA are shown in Figures and , respectively.…”
Section: Antenna Design and Operating Principlementioning
confidence: 99%